Pairs-trading in the stoxx600 - Fartaria, Rafael do Rosário (2022)
This work applies the Pairs-Trading strategy in the European context, namely to the stoxx600 index. This was conducted with daily data over 22 years between 1998 and 2020. The strategy can deliver an average compounded annualized return of 3.62% when the pairs are found by using the prices on the 24-months prior to be traded in the following 6-months. However, it was shown that strategy returns can increase to 5.56% if only 18-months of prices data are used, and the pairs are revaluated at every 3-months. This compares with the 2.44% return on the index for the same period. This study corroborates the argument that the strategy still provides consistent positive returns and increased performance over turbulent periods. It is exposed the importance of trading rules for when the trading period ends.